Application of Developing Test Items for The Elements of Arabic Language in Madrasah Aliyah Level - Andini Nuur Janah Suaibi; Hilwa Wafin Nur; Muharam Hasbi; Sakinah Naziha; Nur Qomari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Evaluation in teaching is one of the important aspects that an educator must do. Evaluation is a benchmark for the success of achievement in planned learning. The process consists of obtaining, analyzing, and interpreting data about the learning process and student learning outcomes. This research aims to provide alternative recommendations for language element test questions consisting of sounds and vocabulary based on the level of Madrasah Aliyah according to the stages of preparing valid and correct tests. This research aims to recommend language element test questions consisting of sounds, vocabulary, and sentence structure based on class levels at Madrasah Aliyah. The steps for writing question items include (1) determining basic competencies, (2) material selection, (3) making indicators, (4) compiling grids, (5) compiling draft questions, (6) reviewing tests, and (7) finalizing. In this article, researchers only write five stages, divided into three simple steps: determining basic competencies and materials, making indicators and compiling test grids, and drafting tests